Knowledge of Dental Health among Mothers of Poor Families during the Pandemic in East Java - Udijanto Tedjosasongko, - (Virtual Commons - Bridgewater State University, 2022)
Mothers play an extremely important role with regards to monitoring the dental health of their children. Hormonal changes associated with pregnancy and poor oral hygiene are responsible for the development of gingivitis. Gingivitis is more common in pregnant women with pre-existing gum problems due to not following careful oral hygiene practices. Identifying mothers with poor oral hygiene and educating them on the importance of their own oral health and that of their unborn child can change previous trajectories of predicted gum disease. The research below focuses on the efforts of pregnant women to optimize the oral hygiene of children under five years of age in poorer communities within the East Java province during the COVID-19 pandemic. Qualitative methods are complemented by quantitative data utilizing a gender perspective. The location of this research centered on: Tomoron village, Omben district, Sampang regency; Bandung Rejosari village, Sukun district, Malang regency; and Gaji village, Kerek district, Tuban regency. The subjects of this study were specifically pregnant women and mothers who have toddlers, as well as health workers from puskesmas (community health centers) and local community leaders in poorer villages. The data were collected through interviews with 180 respondents, consisting of 60 respondents from each research location. The results of this study show: 1) Mothers' knowledge of dental health and their efforts to preserve it during the COVID-19 pandemic; 2) Obstacles faced during this period, which included the lack of socializing and the prohibition on gathering within communities, and their effects on the health of mothers and children. Furthermore, limited services from puskesmas for dental health were found to be detrimental to both children and the general health of the community.